Wedelolactone-Loaded Micelles Ameliorate Doxorubicin-Induced Oxidative Injury in Podocytes by Improving Permeability and Bioavailability - Feng, Liang; Li, Zhi-yong; Wang, Long; Li, Xing-hua; Chen, Ya-ping; Yang, Bing; Yang, Dang; Lian, Yuan-pei; Hou, Xue-feng; Li, Jun-hui; Ding, Shu-min; Jia, Xiao-bin (Frontiers in Bioengineering and Biotechnology, 2019)
Wedelolactone (WED) is commonly used for the treatment of doxorubicin (DOX)-induced kidney damage, but its efficacy is limited by its poor solubility and bioavailability. In this study, we developed a novel delivery system of WED-loaded micelles (WED-M) with Solutol® HS15 and lecithin at an optimized ratio of 7:3 to improve the poor permeability and bioavailability of WED and to enhance its efficacy. The spherically shaped WED-M (particle size: 160.5 ± 3.4 nm; zeta potential: −30.1 ± 0.9 mV; entrapment efficiency: 94.41 ± 1.64%; drug loading: 8.58 ± 0.25%; solubility: 1.89 ± 0.06 mg/ml) has continuous stability over 14 days and a sustained release profile. The permeability of WED-M in Caco-2 cells indicated a significant 1.61-fold higher Papp AP to BL ratio than WED alone. Additionally, pharmacokinetic evaluation of WED-M demonstrated that the bioavailability of WED was increased 2.78-fold. Both HE staining and transmission electron microscopy showed an obvious improvement of pathological damage in WED-M treatment. Moreover, WED-M significantly enhanced the ROS level in mice and MPC5 podocytes. We concluded that using this micelle delivery system for WED could improve its permeability and bioavailability to attenuate DOX-induced oxidative injury in podocytes. This study provided important information on the fact that the micelle delivery system, WED-M, showed a significant improvement of renal damage.